Thenar Muscle Motor Imagery Increases Spinal Motor Neuron Excitability of the Abductor Digiti Minimi Muscle - Bunno, Yoshibumi; Suzuki, Toshiaki (Frontiers in Human Neuroscience, 2021)
When a person attempts intended finger movements, unintended finger movement also occur, a phenomenon called "enslaving". Given that motor imagery (MI) and motor execution share a common neural foundation, we hypothesized that the enslaving effect on the spinal motor neuron excitability occurs during MI. To investigate this hypothesis, electromyography (EMG) and F-wave analysis were conducted in 11 healthy male volunteers. Initially, the EMG activity of the left abductor digiti minimi (ADM) muscle during isometric opposition pinch movement by the left thumb and index finger at 50% maximal effort was compared with EMG activity during the Rest condition. Next, the F-wave and background EMG recordings were performed under the Rest condition, followed by the MI condition. Specifically, in the Rest condition, subjects maintained relaxation. In the MI condition, they imagined isometric left thenar muscle activity at 50% maximal voluntary contraction (MVC). During motor execution, ADM muscle activity was confirmed. During the MI condition, both F-wave persistence and the F-wave/M-wave amplitude ratio obtained from the ADM muscle were significantly increased compared to that obtained during the Rest condition. No difference was observed in the background EMG between the Rest and MI conditions. These results suggest that MI of isometric intended finger muscle activity at 50% MVC facilitates spinal motor neuron excitability corresponding to unintended finger muscle. Furthermore, MI may induce similar modulation of spinal motor neuron excitability as actual movement.